2020
DOI: 10.1007/s10459-020-09965-y
|View full text |Cite
|
Sign up to set email alerts
|

Empathy trajectories throughout medical school: relationships with personality and motives for studying medicine

Abstract: Empathy remains a widely discussed topic within medical education research. Studies on empathy changes among medical students are not univocal: empathy may decline, remain stable or increase. A largely unexplored research question regards inter-individual variability in empathy change, namely if different longitudinal trajectories of empathy exist. Evidence on the association of empathy trajectories with personality and motives for studying medicine is also scarce. Here, latent growth modeling examined empathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 81 publications
1
30
0
3
Order By: Relevance
“…It suggests that some personality traits (openness) as well as patient-oriented motives for studying medicine were associated with higher and stable empathy. 53 Besides, results from studies which use different instruments to analyse medical students' empathy, as IRI and JSE, should be compared cautiously. Both scales measure different but related constructs.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that some personality traits (openness) as well as patient-oriented motives for studying medicine were associated with higher and stable empathy. 53 Besides, results from studies which use different instruments to analyse medical students' empathy, as IRI and JSE, should be compared cautiously. Both scales measure different but related constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Há outros aspectos que contribuem para a mudança dos níveis de empatia ao longo do curso de Medicina além da personalidade e do gênero. Piumatti et al 27 destacam, por exemplo, que a motivação para o estudo da Medicina centrada no paciente pode contribuir para manter a empatia ao longo da formação médica e, por isso, deve ser estimulada.…”
Section: Discussionunclassified
“…Exemplo disso se observa no estudo realizado por Schweller, Costa et al 29 , no qual a aprendizagem por meio de consultas com pacientes simulados favoreceu a empatia de estudantes em diferentes anos do curso de Medicina 29 . Salientamos também a importância de estratégias de aprendizagem precoces para o desenvolvimento da empatia nos estudantes de Medicina, pois, como ressaltam Piumatti et al 27 , alunos com menores níveis de empatia tendem a reduzir ainda mais seu escore com o passar do tempo. Assim, é possível individualizar intervenções pedagógicas integradas ao currículo para mudar esse cenário.…”
Section: Discussionunclassified
“…In a recent article by Piumatti et al, differences in personality and motives of students were attributed to their changes observed in their level of empathy [1]. Empathy is a core tenet of patient-centred care.…”
mentioning
confidence: 99%
“…Traditionally, empathy has been considered an inherent trait, which could not be learned. However, a body of research in educational psychology and pedagogy has demonstrated aptitude for this fundamental attribute can be taught to healthcare providers [1,2]. At present, empathy is a required component education for medical professions.…”
mentioning
confidence: 99%